IMPLEMENTASI METODE FORWARD CHAINING PADA SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT MALARIA PADA PUSKESMAS WAIMANGURA - Inna Dodo, Notria; Elefri Neno, Friden; Fransiska Ledi, Dian (JATI (Jurnal Mahasiswa Teknik Informatika), 2024)
The aim of the expert system was developed to facilitate needs efficiently and quickly thereby reducing the risks that occur. This research has presented an expert system for diagnosing malaria. Malaria occurs due to the cleanliness of the water environment and mosquito bites. In today's technological developments, which are developing so rapidly, expert systems have been introduced in various fields, one of which is human health. Of course, the expert system being developed really requires human intelligence or knowledge that has the expertise to be copied to the computer so that a complex knowledge base is created for decision making. In this research the author has designed an expert system for diagnosing malaria which includes the type of malaria disease, symptoms and solutions. The purpose of the system designed is to help patients in finding information for diagnosing the disease where the patient does not come directly to meet with medical personnel or doctors but Patients can access the system to diagnose diseases according to the complaints that occur. The system diagnosis results will provide information on how to treat them. accurately